A critical review of the progress in prevention and treatment of radiation-induced skin damage - Kemin, Li; Rutie, Yin (Frontiers in Oncology, 2024)
Radiation therapy was initially used in dermatology to treat various skin diseases, including acne vulgaris, keloids, plantar warts, tinea capitis and hirsutism. Although it is no longer used in the treatment of many of these diseases, radiation therapy still plays a crucial role in the treatment of keloids, skin cancer and solid organ malignancies. In the past 20 years, the widespread use of intensity-modulated radiation therapy has significantly increased in the management of tumor growth in multiple cancer sites and reduced the incidence of complications in normal organs. However, the occurrence and severity of radiation-induced organ complications still significantly affects the quality of life of patients and remains a research hotspot. Skin tissue is the largest area in the human body, serving as both a barrier and a defender. In patients undergoing radiation therapy, skin is often the first tissue that gets damaged. Especially, when the tumor involves the skin or is close to the skin (i.e., skin cancer, head and neck cancer, breast cancer, vulvar cancer), the treatment targets the superficial tissues, and may have inherent adverse effects on the skin. With the increasing incidence of cancer and the widespread use of radiation therapy in cancer treatment, the radiation-induced skin damage has become a serious problem. In this pursuit, the present study provides a review of the progress in the prevention and treatment of radiation-induced skin damage, thereby providing a reference for the prevention and treatment of radiation-induced skin damage.